Peran Keluarga dalam Bermain Peran Terhadap Kemampuan Verbal dan Perkembangan Kognitif Anak Usia 5-6 Tahun di SPS TAAM AL-Hikmah - Neli Siti Nuraisyah; Adinda Kania Hatomi; Budi Iskandar (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early childhood verbal abilities are significantly influenced by stimulation provided in the family environment, one of which is through role-playing activities. This study aims to describe the role of the family in role-playing activities as a stimulation of verbal abilities in children aged 5–6 years, and to identify its impact on children's cognitive development based on differences in the intensity of parental involvement. The method used was a qualitative case study design. The research subjects consisted of two children aged 5–6 years who were selected purposively with a maximum variation strategy: one child with active family involvement in role-playing (FZ) and one child with less active family involvement (FT). Data collection was carried out through direct observation, in-depth semi-structured interviews with parents and teachers, and documentation. Data analysis used the Miles and Huberman model with source triangulation techniques. The results showed that children with active family involvement in role- playing showed more developed verbal abilities, high learning initiative, and more optimal cognitive development. Conversely, children with less active family involvement tended to be verbally passive, less independent, and showed more limited cognitive development due to the dominance of unsupervised gadget use. This study confirms that active family involvement in role-playing activities plays an important role in stimulating children's verbal and cognitive growth and development